2015
DOI: 10.1007/s10661-015-4487-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of phytoplankton growth and grazing loss in the west coast of Peninsular Malaysia

Abstract: Phytoplankton growth (µ) and grazing loss (g) rates were measured monthly by the Landry-Hassett dilution method over a two-year period at both estuarine (Klang) and study, grazing loss was coupled to phytoplankton growth and the ratio of g : μ or grazing pressure which estimates the proportion of primary production grazed was 50% at Klang and lower than at Port Dickson (68%) (t = 2.213, df = 36, p < 0.05). We found that the higher growth rates in an eutrophic system i.e. Klang were not matched by higher gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…3): very low values (<0.5 μmol l − 1 DIN) are seen especially during the late NE monsoon and intermonsoon 1, which are similar to reports from the open Sunda Shelf and the South China Sea (Kartadikaria et al, 2015;Liu et al, 2020;Ning et al, 2004). In contrast, nutrient concentrations during the SW monsoon are significantly elevated, and similar to values reported from the Malacca Strait (Lim et al, 2015(Lim et al, , 2021. However, chlorophyll-a concentrations were above 0.4 μg l − 1 in all but two samples, and averaged about 1 μg l − 1 (Fig.…”
Section: Seasonality and Range In Dissolved Nutrient Concentrationssupporting
confidence: 85%
See 1 more Smart Citation
“…3): very low values (<0.5 μmol l − 1 DIN) are seen especially during the late NE monsoon and intermonsoon 1, which are similar to reports from the open Sunda Shelf and the South China Sea (Kartadikaria et al, 2015;Liu et al, 2020;Ning et al, 2004). In contrast, nutrient concentrations during the SW monsoon are significantly elevated, and similar to values reported from the Malacca Strait (Lim et al, 2015(Lim et al, , 2021. However, chlorophyll-a concentrations were above 0.4 μg l − 1 in all but two samples, and averaged about 1 μg l − 1 (Fig.…”
Section: Seasonality and Range In Dissolved Nutrient Concentrationssupporting
confidence: 85%
“…Closer to shore and within estuaries, significant levels of eutrophication due to nutrient input have been reported, with chlorophyll-a of 5-50 μg l − 1 at some sites (Chai et al, 2021;Damar et al, 2019;Lim et al, 2018Lim et al, , 2021Tomascik et al, 1994). However, very few studies have collected multi-year biogeochemical time series in Southeast Asia (Lim et al, 2015(Lim et al, , 2018. This hampers our understanding of the drivers of coastal biogeochemistry in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, numerous SA coastal areas have experienced pollution and excessive chlorophyll-a levels. Lim et al (2015) reported that the coastal water systems along the Malacca straits has chlorophyll-a level up to 2.76 mg/m 3. Another SA coastal area deserves attention is located in Jakarta.…”
mentioning
confidence: 99%
“…The prevailing poor water quality in nearshore waters as indicated by low dissolved oxygen concentrations close to hypoxia and high total suspended solids (TSS) have also been documented ( Lee & Bong, 2006 ). The Klang Strait has been classified as a eutrophic environment with episodic phytoplankton blooms and high bacteria abundance ( Lee & Bong, 2006 ; Lee, Bong & Hii, 2009 ; Lim, Lee & Kudo, 2015 ). While there are no marked changes in deep water fish production, the catch per unit effort of coastal fisheries due to shrimp and bag net catches has dropped dramatically since the mid-1990s despite little change in the fishing effort (see ).…”
Section: Introductionmentioning
confidence: 99%